Development and psychometric properties of a new social support scale for self-care in middle-aged patients with type II diabetes (S4-MAD) - Naderimagham Shohreh; Niknami Shamsaddin; Abolhassani Farid; Hajizadeh Ebrahim; Montazeri Ali (BMC, 2012)
Abstract Background Social support has proved to be one of the most effective factors on the success of diabetic self-care. This study aimed to develop a scale for evaluating social support for self-care in middle-aged patients (30-60 years old) with type II diabetes. Methods This was a two-phase qualitative and quantitative study. The study was conducted during 2009 to 2011 in Tehran, Iran. In the qualitative part, a sample of diabetic patients participated in four focus group discussions in order to develop a preliminary item pool. Consequently, content and face validity were performed to provide a pre-final version of the questionnaire. Then, in a quantitative study, reliability (internal consistency and test-retest analysis), validity and factor analysis (both exploratory and confirmatory) were performed to assess psychometric properties of the scale. Results A 38-item questionnaire was developed through the qualitative phase. It was reduced to a 33-item after content validity. Exploratory factor analysis loaded a 30-item with a five-factor solution (nutrition, physical activity, self monitoring of blood glucose, foot care and smoking) that jointly accounted for 72.3% of observed variance. The confirmatory factor analysis indicated a good fit to the data. The Cronbach's alpha coefficient showed excellent internal consistency (alpha=0.94), and test-retest of the scale with 2-weeks intervals indicated an appropriate stability for the scale (ICC=0.87). Conclusion The findings showed that the designed questionnaire was a valid and reliable instrument for measuring social support for self-care in middle-aged patients with type II diabetes. It is an easy to use questionnaire and contains the most significant diabetes related behaviors that need continuous support for self-care.